PREDICTION OF SOUTHERN OSCILLATION USING THE INDONESIAN THROUGHFLOW VARIABILITY - Aldrian, Edvin; Arifian, Jon (Marine Research in Indonesia, 2009)
Atmospheric boundary layer derived from NCEP/NCAR reanalyses for the period of 1974 to 2002 has been used as boundary forcings for the global ocean model Max Planck Institute Ocean Model (MPIOM). The ocean model is a curvilinear grid model, whose poles are located over mainland China and over the Australian continent, thus focusing on the maritime continent. The model simulates major Indonesian throughflow passages that focus on six cannels representing three inlets and three outlets (the Makassar, Lifamatola, Halmahera, Lombok, Ombai and Timor Straits). The model results have been validated using the Arlindo observation Project over the Makassar Strait in the period of January 1997 to February 1998, which fortunately was during a strong El NiÃ±o episode. The model simulation results were then investigated for their prediction capabilities of any of those channels in foreseeing the incoming southern oscillation events. Temporal correlation analysis with lag and advance time correlation methods were performed against simulated data at all levels on those channels. Variabilities in depth of 74 to 200m (thermocline depth) show the strongest correlation with SOI index (Darwin minus Tahiti mean sea level pressure). The temperature and salinity correlations with SOI are the highest with one-month in advance over Lifamatola Strait (0.77) and two-month in advance over the Makassar Straits (0.74). These significant correlations highlight the important of those two straits in prediction of incoming southern oscillation that usually leads to ENSO episode which brings most of the time devastating impact to economy, agriculture and ecosystem.